2005
DOI: 10.1017/s096719940500331x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and ultrastructure of gene-microinjected rabbit embryos after vitrification

Abstract: Morphological signs of injury and subsequent regeneration following vitrification of either rabbit gene microinjected (Gene-Mi) or intact in vitro cultured embryos derived from in vivo fertilized eggs were evaluated by post-warming recovery in culture and analysed by transmission electron microscopy (TEM). The percentages of vitrified/warmed Gene-Mi embryos that reached the blastocyst stage (69%) and hatched (57%) did not differ significantly from those of intact embryos (78% and 56%, respectively). In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Microinjection of the gene construct in the study of Makarevich et al (2006) did not affect the cleavage rate of embryos, but blastocyst rate was significantly lowered compared with intact embryos. Popelková et al (2005) reported that the ability to achieve the hatching in microinjected rabbit blastocysts (94.00%) is comparable with the control group of embryos (90.00%). Microinjection of a foreign gene into the pronucleus of eggs can result in chromosomal aneuploidy (Roychoudhury et al, 2008), and DNA rearrangement during integration can cause decreased yield of blastocyst stage embryos (Voss et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Microinjection of the gene construct in the study of Makarevich et al (2006) did not affect the cleavage rate of embryos, but blastocyst rate was significantly lowered compared with intact embryos. Popelková et al (2005) reported that the ability to achieve the hatching in microinjected rabbit blastocysts (94.00%) is comparable with the control group of embryos (90.00%). Microinjection of a foreign gene into the pronucleus of eggs can result in chromosomal aneuploidy (Roychoudhury et al, 2008), and DNA rearrangement during integration can cause decreased yield of blastocyst stage embryos (Voss et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
“…Kasai et al (1992) reported that 96.00% of vitrified rabbit morulae had intact zona pellucida after thawing. Popelková et al (2005) used DMSO as a cryoprotectant and did not find significant difference in the developmental rate of rabbit embryos, because 57.00% of vitrified and 56.00% of intact rabbit embryos reached the hatching blastocyst stage. Results obtained by Papis et al (2005) are also comparable with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotolerance may be a useful indicator of blastocyst quality (Rizos et al, 2001). As a functional criteria for the evaluation of embryo viability after cryopreservation, a post-thaw cleavage up to blastocyst stage (Popelkova et al, 2005;Makarevich et al 2008), embryo cell number and embryo diameter (Popelkova et al, 2009), proliferation (PCNA) index (Markkula et al, 2001) or number of apoptotic (TUNEL) cells (Marquez-Alvarado et al, 2004;Makarevich et al, 2008) and the state of actin cytoskeleton (Tharasanit et al 2005;Makarevich et al, 2008) have been used.…”
Section: Introductionmentioning
confidence: 99%
“…An optimum content of vitrification solution(s) fulfilling embryo demand for cryoprotective efficacy and low toxicity has been of interest to researchers for years. Decreasing the toxicity was realised in part by the addition of sugars to vitrification solutions (Kasai et al, 1992;Ali and Shelton, 1993;Hochi et al, 2004;Popelkova et al, 2005) or, more specifically, by replacement of a proportion of permeating compounds by sucrose (Papis et al, 1993). Minimum sample size (or minimum volume) vitrification systems successfully applied for mammalian embryos (Vajta et al, 1998;Papis et al, 1999) combined with the use of supercooled liquid nitrogen (cooled down to about -206 °C, e.g.…”
mentioning
confidence: 99%
“…Only few of the vitrification solutions applied for rabbit embryos contain an addition of sucrose (Kasai et al, 1992;Papis et al, 1993;Hochi et al, 2004;Popelkova et al, 2005) which does not permeate into the cells, but increases the vitrification capability of the given solution and, more significantly, causes dehydration of cells due to the hyperosmotic properties of sucrose solution. VM used in the present study contains the lowest ratio of permeating agents described until now for traditional (not minimum volume) vitrification.…”
mentioning
confidence: 99%